Tourism commodification and privatization of nature: private protected areas in the Serra de Tramuntana (Mallorca) - Nora Müller; Robert Fletcher; Macià Blázquez Salom (Boletín de la Asociación de Geógrafos Españoles, 2023)
The creation of private protected areas (PPA) is commonly considered an instrument of neoliberal conservation, characterized by private management and commodification of nature for (eco)tourism and other market-based instruments (MBIs). PPAs are accused of reproducing social inequalities when entailing enclosure, exclusivity, land grabbing or dispossession. Yet PPAs exist in many different forms that enact these various processes in different ways. Our research explores this variegation in PPAs by offering a more nuanced understanding of the often complex and contradictory interconnections between processes of commodification and privatization different PPAs enact, as well as how PPAs are often operationalized differently in global south and north contexts. To develop this analysis, we draw on the conceptual framework of commodification proposed by Castree (2003) to investigate a number of PPAs located in the Serra de Tramuntana mountain range on the island of Mallorca in Spain. Our results show that commodification and privatization combine in different ways and to different degrees in the various PPAs in this area. Overall, we conclude, privatization appears more pervasive than commodification in this global north context, as compared to research concerning PPAs in the global south suggesting the presence of far more commodification in such lower-income contexts.